Inhibition of EGFR Pathway Suppresses M1 Macrophage Polarization and Osteoclastogenesis, Mitigating Titanium Particle-Induced Bone Resorption - Jia Q; Liu L; Yu Y; Wulamu W; Jia L; Liu B; Zheng H; Peng Z; Zhang X; Zhu R (Dove Medical Press, 2024)
Qiyu Jia,1,* Lu Liu,1,* Yunyuan Yu,2,* Wuhuzi Wulamu,1 Lin Jia,1 Bo Liu,1 Hao Zheng,3 Zhenlei Peng,1 Xiaogang Zhang,1 Ruixia Zhu2 1The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People's Republic of China; 2Department of orthopedics, the Affiliated Changzhou Second People's Hospital of Nanjing Medical University, Changzhou, People's Republic of China; 3The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Ruixia Zhu, Department of Orthopaedics, the Affiliated Changzhou No.2 People's Hospital of Nanjing Medical University, 29 Xinglong Alley, Changzhou, 213003, People's Republic of China, Email ZRX_1982@sina.com Xiaogang Zhang, The First Affiliated Hospital of Xinjiang Medical University, 137 Liyue Shan South Road, Xinshi District, Urumqi, 830054, People's Republic of China, Email zxgjohn1972@sina.comPurpose: The polarization of macrophages towards the pro-inflammatory M1 phenotype and osteoclast overactivation play a significant role in the pathogenesis of aseptic loosening of orthopedic implants. This study sought to examine the expression and activation of macrophages and osteoclasts in implant biopsies with respect to epidermal growth factor receptor (EGFR) signaling and to assess the potential of EGFR inhibition in mitigating titanium particle-induced bone resorption in a cranial resorption murine model.Methods: Bone marrow-derived macrophages (BMDMs) were stimulated with Tumor Necrosis Factor-alpha (TNF-α) and Interferon-gamma (IFN-γ) initially. Subsequently, Osteoclast differentiation was initiated after Gefitinib was added to the treatment groups. Male C57BL/6 mice were treated with Gefitinib or 0.5% Carboxymethyl Cellulose-Sodium (CMC-Na) by oral gavage daily for two weeks. A sham group received no further intervention, while the other groups had titanium particles implanted. Tissues were collected and analyzed by measurements such as micro-computed tomography (micro-CT) analyses, histology, immunofluorescence stainings, cell viability assays, assays for resorption pit formation, Reverse Transcription-Polymerase Chain Reactions (RT-PCRs), and Western blots were conducted.Results: The study demonstrated a significant upregulation of EGFR in response to titanium particle exposure. Inhibition of EGFR phosphorylation with gefitinib effectively reduced bone degradation at osteolytic sites in a murine model. Gefitinib treatment led to a notable reduction in M1 macrophage polarization, as indicated by immunofluorescence staining and Western blot analysis of macrophage markers. Mechanistically, selective EGFR inhibitors mitigate osteoclastogenesis and osteoclast resorption by inhibiting the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and nuclear factor-κB (NF-κB) signaling pathways.Conclusion: Our findings provide compelling evidence of the essential role of EGFR-related pathways in M1 polarization, osteoclast activation, and ensuing periprosthetic osteolysis. Overall, EGFR presents a novel target for addressing bone resorption-associated conditions triggered by particles or modulated by macrophages and osteoclasts.Keywords: EGFR, Wear particles, osteoclast, bone resorption, macrophage polarization